Informática na educação e o Ensino de Ciências Naturais: contribuições para a educação ambiental no contexto Amazônico - Silva, Rosa Eulália Vital da (2009)
Computer science in the education is one of the thematic ones that more they involve education, the research and learning in the present time, since is resulted of the cultural production of the humanity, influencing habits, values and chancing a change of position ahead of the scene that if presents in the educational context, in the scientific world, a search to interdisciplinary present in the research and the education of Sciences. In this research basic elements are argued involving the tripod: Computer science in the Education, Education of Sciences and Ambient Education. In this research basic elements are argued involving the tripod: Computer science in the Education, Education of Sciences and Ambient Education. The same one integrates pertinent subjects the Education; Society, Education, Education, Science and Technology: a necessary joint in the educative process, that aims at to the construction of the autonomy and the participation of the professors in world each more technological time. Having as objective generality to consider a called educational program of RECIENCIAS (Net of Interactive Communication in Natural Science Education) mediated by the use of the computer having as technological support to the Internet, as didacticpedagogical resource for Natural Science Education in order to contribute with the Ambient Education for the agreement of the complexity of the Amazonian context. Therefore it developed the following specific objectives: diagnosis of the use of the computational resources in Natural Science Education; identification of the potentialities of the computational resources that integrate the pertaining schools to the State Net of Education, as has supported the proposal innovative in Natural Science Education the elaboration of the proposal methodological of the RECIENCIAS. In this study the citizens are the professors of Basic Education of 6° to 9° year who act in the scope of the Secretariat of Education of the State of Amazon in the following cities: Urucará, Nhamundá, Itacoatiara and Manaus. One is about a qualitative research, allowing to consider the experiences of the point of view of the citizens, establishing one I dialogue and a boarding that is not neutral. The data had been collected through a composed questionnaire of opened questions, have seen that this type of question allows to the free expression of the subject front to the questionings on its practical professional. The data had been analyzed according to technique of Categories of Codification as considered by Bogdan and Bicklen (1994). It was evidenced necessity to develop a pedagogical space, of quarrels, information, knowledge, education, education and learning, that made possible to the professor the insertion, interaction and communication of new methodologies in the construction of the knowledge. In sight of displayed of the constitution of the Amazonian scene of the challenges and the potentialities it is that the RECIENCIAS - in a space of production of digital pedagogical contents is proven, stimulating the participation of the professors and students to construct to new knowledge and pedagogical didactic concepts in interactive nets, for the access to the world-wide net of computers, promoting the qualification of these professors in free courses for the development of Natural Science Education